How foreign language affects decisions: Rethinking the brain-drain model - Hadjichristidis, Constantinos; Geipel, Janet; Surian, Luca (Journal of International Business Studies, 2017)
Volk, Köhler, & Pudelko (JIBS 45:862–885, 2014) propose that foreign language use depletes cognitive resources, thus hindering individual decision making and self-regulation. The present commentary highlights studies showing that foreign language use can also improve decision making and self-regulation. We propose that these benefits derive from two psychological factors. The first concerns the timing of cognitive depletion. Foreign language use involves an increase of memory load in the early phases of information processing, which has been shown to reduce the capture of attention by tempting stimuli. The second factor concerns the nature of human memory. Experiences and their associated emotions are coded in the language in which they occur, and thus are more accessible when the same language is used at retrieval. Therefore certain mental constructs, such as stereotypes, which have been shaped by years of cultural learning in a native language context, may exert less influence when processing a foreign language. The present treatment indicates value in extending Volk et al.’s conceptual model, and can help develop language strategies that may ultimately improve organizational decision making.